2014
DOI: 10.1021/jp5033965
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Water Splitting by Plasmonic TiO2–Fe2O3 Cocatalyst under Visible Light Irradiation

Abstract: In this study, we introduce a plasmonic TiO2–Fe2O3 cocatalyst photoelectrode to improve the water-splitting process. The absorption of incident photons and the separation rate of photogenerated electron–hole pairs are enhanced due to the broadband absorption and strong electric field of the composite formed from these two metal oxide semiconductors and plasmonic silver nanoparticles (Ag NPs). Plasmonic TiO2–Fe2O3 cocatalyst photoelectrodes were fabricated using a precipitation and solution processing method. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 36 publications
(39 reference statements)
2
53
1
2
Order By: Relevance
“…Thus, structural deformations and presence of defects in the TiO 2 crystals might have formed by the substitution of Ti 4+ by Fe 3+ , which marginally reduces the crystallinity of TiO 2 [8]. As noted earlier, in composites with above 25% content of Fe 2 O 3 in TiO 2 , anatase TiO 2 peaks start diminishing while peaks for rutile phase start appearing.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 81%
See 3 more Smart Citations
“…Thus, structural deformations and presence of defects in the TiO 2 crystals might have formed by the substitution of Ti 4+ by Fe 3+ , which marginally reduces the crystallinity of TiO 2 [8]. As noted earlier, in composites with above 25% content of Fe 2 O 3 in TiO 2 , anatase TiO 2 peaks start diminishing while peaks for rutile phase start appearing.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 81%
“…It is found that chemical synthetic route and parameters involved in the entire synthesis of TiO 2 -Fe 2 O 3 materials have a significant effect on the morphology, porous structure and phase structure. Some research works have delicately reported the synthesis of TiO 2 -Fe 2 O 3 using solgel process from chloride precursor [7][8][9][10], but no available work reports the presented water based sol-gel method and with the physicochemical properties for both oxides revealed in the present study. The photocatalytic activity of prepared fine powders was tested in the reaction for degradation of methylene blue dye.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Former studies on Fe 2 O 3 /TiO 2 heterostructures have also observed a more efficient separation of electron-hole pairs. [45,46] On the other hand, the band alignment also leads to a barrier for hole transport towards the surface and is therefore detrimental to high photocurrents. For this reason we propose that the efficiency of a coated hematite photoelectrode could be improved by employing a material for the over layer where the band alignment not only favors fast electron depletion at the surface but also fast hole transport towards the surface.…”
Section: Resultsmentioning
confidence: 99%